2014
DOI: 10.17508/cjfst.2014.6.2.05
|View full text |Cite
|
Sign up to set email alerts
|

Effect of apple by-product as a supplement on antioxidant activity and quality parameters of pasta

Abstract: Indexing p. 1  Editorial Bord p. 1  Guide for Authors p. 3  Manuscript preparation p. 5

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(30 citation statements)
references
References 25 publications
2
28
0
Order By: Relevance
“…A similar result was obtained in pasta with okara powder (Pan, Liu and Shiau, 2018;Kamble et al, 2019), partially-deoiled chia flour (Aranibar et al, 2018), grape and pomegranate seeds powder (Koca et al, 2018), and apple and mango peel powder (Lončarić et al, 2014;Jalgaonkar, Jha and Mahawar, 2018). Instead, Zarzycki et al (2020), Sykut-Domanska et al (2020 and Nocente et al, (2021) observed an increase in OCT in pasta fortified with deoiled flaxseed, coconut flours, and brewers' spent grain.…”
Section: Accepted Articlementioning
confidence: 53%
See 1 more Smart Citation
“…A similar result was obtained in pasta with okara powder (Pan, Liu and Shiau, 2018;Kamble et al, 2019), partially-deoiled chia flour (Aranibar et al, 2018), grape and pomegranate seeds powder (Koca et al, 2018), and apple and mango peel powder (Lončarić et al, 2014;Jalgaonkar, Jha and Mahawar, 2018). Instead, Zarzycki et al (2020), Sykut-Domanska et al (2020 and Nocente et al, (2021) observed an increase in OCT in pasta fortified with deoiled flaxseed, coconut flours, and brewers' spent grain.…”
Section: Accepted Articlementioning
confidence: 53%
“…All rights reserved oxygen and UV light exposure (Guaita et al, 2021). Alternatively, freeze-drying can be used to reduce the moisture of the by-products as performed by Simonato et al (2019) for olive pomace and by Lončarić et al (2014) for apple peel. However, different authors observed that for grape pomace, the drying treatment gave a better result in terms of retaining bioactive compounds content (García-Lomillo and González-SanJosé, 2017;Tolve et al, 2020).…”
Section: Accepted Articlementioning
confidence: 99%
“…Regarding the cooked samples, the pasta with 15% OPF recorded low elasticity and firmness, thus receiving a global score for overall quality slightly under the acceptability threshold (4.42). Most probably, this is due to the inclusion of fibers from olive paste that promoted the formation of discontinuities or cracks in the pasta strand, thus weakening its structure [ 28 ]. A weak or discontinuous protein matrix results in a protein network that is too loose and permits greater amount of leaching during starch granule gelatinization, causing increased adhesiveness and bulkiness [ 12 ].…”
Section: Resultsmentioning
confidence: 99%
“…Increase of water absorption and swelling index with OPF addition could be explained by the high fiber content addition. Lončarić [ 28 ] also observed a rise in water absorption for pasta enriched with apple flour with respect to control pasta. The addition of TG caused a decline of these two parameters.…”
Section: Resultsmentioning
confidence: 99%
“…Apples are known as a good source of phenolic compounds [79], especially the peel [80]. According to the investigations of Lončarić et al [39] incorporation of apple peel powder in pasta has increased the content of total polyphenols content and antioxidant activity significantly than in conventional pasta. However, it has increased the cooking loss and water absorption and has decreased the adhesiveness, hardness and sensory qualities of pasta.…”
Section: Antioxidants Supplemented Pastamentioning
confidence: 99%